Analisis Adaptasi dan Biaya Adaptasi Masyarakat Desa Sriwulan terhadap Banjir Rob - Nabilah Kamal (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
As a coastal area, Sriwulan Village in Sayung District, Demak Regency, often faces increasingly severe tidal flooding problems. To survive, the people in this village have developed various adaptation methods in their social, economic, and physical lives. This study aimed to describe in detail the adaptations implemented by the residents of Sriwulan Village and measure the costs they have to spend to deal with the impact of tidal flooding. This research was conducted from January to August 2022. This research was conducted from January to August 2022 with a rationalistic deductive qualitative approach. The research sample consisted of 10 respondents representing the people of Sriwulan Village. The variables studied included the form of adaptation (physical, social, economic) and the amount of adaptation costs calculated using the averting behavior method. The study results showed that the total adaptation costs incurred by all respondents over the past 20 years reached IDR 663,010,000.